FRI0199 EFFECTIVENESS AND SAFETY OF BELIMUMAB IN PATIENTSWITH ACTIVE SYSTEMIC LUPUS ERYTHEMATOSUS: RESULTS FROM A LARGE, NATIONWIDE, MULTICENTRIC STUDY. (June 2019) - Iaccarino, Luca; Saccon, Francesca; Mathieu, Alessandro; Piga, Matteo; Ceribelli, Angela; Selmi, Carlo; Cardinaletti, Paolo; Gabrielli, Armando; Matteo, Andrea DI; Angelis, Rossella De; Faggioli, Paola; Laria, Antonella; et al.
Abstract : Background: Belimumab is the unique biologic therapy available for patients with SLE. Objectives: To investigate effectiveness and safety of belimumab in SLE patients in clinical practice. Methods: 458 active SLE patients (ACR criteria) from 24 Italian Centers, mean±SD age 43.5±11.3 years; mean±SD disease duration 12.3±8.7 years, were treated with belimumab (10 mg/kg day 0, 14, 28 and then every 28 days), as add-on therapy. SLEDAI-2K, anti-dsDNA, C3, C4, prednisone daily dose, DAS-28, 24H proteinuria, CLASI, PGA, Fatigue (VAS 0-10) were recorded at baseline and every 6 months. Flares were defined according to SFI. Response was evaluated according to SRI-4. Statistics were performed by pairs T-test, chi-square test and multiple logistic regression (SPSS, version 22.0). Results: Mean±SD follow-up was 21.2±15.3 months (range 3-60). Most common features treated with belimumab were articular in 67%, mucocutaneous in 55%, and renal in 17% of cases. Improvement of clinical and serological variables, including daily prednisone dosage, was observed (Table). SRI-4 is summarized in the Figure. At the end of follow-up 293 patients (66%) were still on belimumab. Most common cause of discontinuation were inadequate response (36%), AEs (31%), and pregnancy (8%). Mean number of flare during belimumab treatment compared with the corresponding period before belimumab initiation decreased (p<0.001). SLEDAI-2K ≥10 was an independent predictor of response by logistic regression at month 12 and 24 (p=0.003 and p=0.025). 9, 998 infusions were analyzed. 784 AEs were observed in 330 patients, SAEs were 43 in 36 patients. No severe infusion reactions were observed; 16 patients had infective SAEs, and 22 non infective SAEs. Conclusion: We confirmed the effectiveness, the steroid sparing effect and good safety profile of belimumab in our cohort. Disclosure of Interests: Luca Iaccarino: None declared, Francesca Saccon: None declared, Alessandro Mathieu: None declared, Matteo Piga: None declared, Angela Ceribelli: None declared, Carlo Selmi Grant/research support from: Abbvie, Janssen, MSD, Novartis, Pfizer, Consultant for: Abbvie, Alfa-Sigma, Biogen, BMS, Celgene, Eli-Lilly, GSK, Janssen, Merck Sharp and Dohme, Novartis, Pfizer, Roche, Sanofi-Genzyme, YCB, Speakers bureau: Abbvie, Alfa-Sigma, Biogen, BMS, Celgene, Eli-Lilly, GSK, Janssen, Merck Sharp and Dohme, Novartis, Pfizer, Roche, Sanofi-Genzyme, YCB, Paolo Cardinaletti: None declared, Armando Gabrielli: None declared, Andrea Di Matteo: None declared, Rossella De Angelis: None declared, Paola Faggioli: None declared, Antonella Laria: None declared, Micaela Fredi: None declared, Francesca Regola: None declared, Laura Andreoli: None declared, Giulia Pazzola: None declared, Carlo Salvarani: None declared, Francesco Puppo: None declared, Simone Negrini: None declared, Marcella Prete: None declared, Vito Racanelli: None declared, Elisa Gremese Consultant for: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Sanofi, UCB, Roche, and Pfizer, Speakers bureau: BMS, Speakers bureau: Roche, Speakers bureau: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Sanofi, UCB, Roche, and Pfizer, Maria Gerosa: None declared, Tania Ubiali: None declared, Enrica Bozzolo: None declared, Valentina Canti: None declared, Fabrizio Conti: None declared, Fulvia Ceccarelli: None declared, Elena Bartoloni Bocci: None declared, Roberto Gerli: None declared, Antonio Lobasso: None declared, Amato De Paulis: None declared, Ginevra De Marchi: None declared, Salvatore De Vita Grant/research support from: Roche, Pfizer, Abbvie, Novartis, BMS, MSD, Celgene, Janssen, Consultant for: Roche, Alessandra Bortoluzzi: None declared, Marcello Govoni Paid instructor for: Pfizer, Roche, Speakers bureau: Pfizer, Abbvie, MSD, Roche, Eli-Lilly, Celgene, Sanofi, Janssen, Francesco Benvenuti: None declared, Margherita Zen: None declared, Marta Mosca Paid instructor for: GlaxoSmithKline, Lilly, UCB, Chiara Tani: None declared, Maurizio Rossini: None declared, Giovanni Orsolini Speakers bureau: Grunenthal, Mariele Gatto: None declared, Salvatore Scarpato: None declared, Enrico Brunetta: None declared, Aurora Zumbo: None declared, Gabriele Valentini: None declared, SERENA FASANO: None declared, Giacomo Emmi: None declared, Maria Letizia Urban: None declared, Giacomo Tanti: None declared, Angela Tincani Consultant for: UCB, Pfizer, Abbvie, BMS, Sanofi, Roche, GSK, AlphaSigma, Lillly, Jannsen, Cellgene, Novartis, Andrea Doria: None declared